Acute effect of statins on vascular reactivity in maternal and placental arteries from pregnancies complicated by preeclampsia - Agwu, Chinedu; Myers, Jenny; Wareing, Mark; Dilworth, Mark (Frontiers in Physiology, 2025)
IntroductionThis study aimed to investigate the acute effects of statins on maternal and fetoplacental vascular reactivity in vessels from pregnancies affected by pre-eclampsia (PE), a leading cause of maternal and fetal morbidity and mortality. Statins have been proposed as a candidate therapy due to their pleiotropic effects but evidence of statins’ ability to ameliorate the observed endothelial dysfunction in PE is lacking.MethodsHuman chorionic plate arteries (CPAs) and omental arteries (OAs) from normal and PE pregnancies were mounted on a wire myograph. Contraction was assessed with KPSS and the thromboxane mimetic U46619. Arteries were incubated for 2 h with 1 µM or 10 µM pravastatin, pitavastatin or simvastatin (pitavastatin only in OAs). U46619 dose–response curves were repeated or dose-response curves with NO-donor SNP or endothelium-dependent bradykinin (BK) performed following U46619 pre-constriction.ResultsCPAs from normal and PE pregnancies showed similar responses following exposure to the vasoconstrictive agent U46619 and the relaxatory agent SNP. Short-term exposure to pravastatin, simvastatin and pitavastatin did not cause detrimental effects on CPA reactivity. Acute exposure of OAs from PE pregnancies to pitavastatin (1 µM) did not reduce U46619-mediated contraction or enhance BK-mediated relaxation of vessels although in this study ex vivo endothelial function of OAs from PE pregnancies was not different to those in normotensive pregnancy pre incubation.DiscussionIn conclusion, this study did not demonstrate an effect on vascular reactivity of maternal systemic or fetoplacental arteries following acute treatment of statins. Future studies investigating the effect of longer-term statin exposure on maternal and fetoplacental vascular reactivity may help towards treatment strategies for vascular dysfunction in PE-affected patients.